2008
DOI: 10.1007/s00445-008-0242-x
|View full text |Cite
|
Sign up to set email alerts
|

Landslide and tsunami hazard at Yate volcano, Chile as an example of edifice destruction on strike-slip fault zones

Abstract: ▶ Covers volcanoes, their products, their eruptive behavior, and their hazards ▶ Aims to improve understanding of the deeper structure of volcanoes, and the evolution of magmatic systems ▶ Official journal of the International Association of Volcanology and Chemistry of the Earth's Interior (IAVCEI) ▶ 100% of authors who answered a survey reported that they would definitely publish or probably publish in the journal again

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
6
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 24 publications
(7 citation statements)
references
References 41 publications
1
6
0
Order By: Relevance
“…The occurrence of subaerial and/or subaqueous mass-wasting events has frequently been linked to the generation of lacustrine tsunamis (Plafker and Eyzaguirre, 1979;Schnellmann et al, 2002Schnellmann et al, , 2006Hermanns et al, 2004;Girardclos et al, 2007;Villarosa et al, 2009;Watt et al, 2009;Dirksen et al, 2011;Strasser et al, 2011;Kremer et al, 2012; A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT Roberts et al, 2013;Lindhorst et al, 2014). The morphometric analysis of subaqueous landslides is therefore a useful tool that provides insight into tsunami hazards (McAdoo and Watts, 2004) for the lakeshore communities.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The occurrence of subaerial and/or subaqueous mass-wasting events has frequently been linked to the generation of lacustrine tsunamis (Plafker and Eyzaguirre, 1979;Schnellmann et al, 2002Schnellmann et al, , 2006Hermanns et al, 2004;Girardclos et al, 2007;Villarosa et al, 2009;Watt et al, 2009;Dirksen et al, 2011;Strasser et al, 2011;Kremer et al, 2012; A C C E P T E D M A N U S C R I P T ACCEPTED MANUSCRIPT Roberts et al, 2013;Lindhorst et al, 2014). The morphometric analysis of subaqueous landslides is therefore a useful tool that provides insight into tsunami hazards (McAdoo and Watts, 2004) for the lakeshore communities.…”
Section: Accepted M Manuscriptmentioning
confidence: 99%
“…The upper basin of the Reloncaví Fjord between the Petrohué and Puelo deltas, follows the Liquine-Ofqui Fault Zone (Fig. 1a), which is a major transpressional system with associated Quaternary volcanoes (Lange et al, 2008;Cembrano and Lara, 2009), along which earthquakes ruptures (e.g., the last 2007 Moment magnitude (M w ) 6.2 event; Legrand et al, 2011;Vargas et al, 2013) trigger landslides on land, in lakes and in the fjords (Chapron et al, 2006;Watt et al, 2009;St-Onge et al, 2012;Van Daele et al, 2013). In addition, large subduction earthquakes affected the area in CE 2010 (M w 8.8), CE 1960 (M w 9.5), CE 1837, CE 1737, and CE 1575; all of them, except for the CE 1737 event, were related to very long rupture zones and were capable of generating tsunamis in some of the fjords and in the adjacent Pacific Ocean (e.g., Cisternas et al, 2005;St-Onge et al, 2012).…”
Section: Geologymentioning
confidence: 99%
“…1a) are located in the vicinity of the Reloncaví Fjord (Fontijn et al, 2014). Edifice collapse generating landslides are a major hazard posed by many volcanoes (e.g., Watt et al, 2009).…”
Section: Geologymentioning
confidence: 99%
“…trenching studies). Following recent work describing faults that traverse volcanoes (Lagmay et al 2000;Wooler 2003;Palomo et al 2004;Norini et al 2008;Watt et al 2009;Tibaldi et al 2010), the faults identified in the SW edifice of Natib are interpreted as the extension of the Lubao Fault of Siringan & Rodolfo (2003) and Soria (2009). Both structures are collinear and have the same orientation.…”
Section: Structuresmentioning
confidence: 99%
“…Many faults that traverse volcanoes have been reported in the literature (Wooler 2003;Palomo et al 2004;Norini et al 2008;Watt et al 2009;Tibaldi et al 2010). A classic example is Mayon Volcano, which is traversed by the northern bounding fault of the Oas Graben (Lagmay et al 2005;Lagmay & Zebker 2009).…”
Section: Evaluation Of Seismic and Tectonic Hazardsmentioning
confidence: 99%